A relação do Programa Bolsa Família com a evolução dos indicadores sociais de combate à pobreza no Rio Grande do Sul: um olhar a partir da abordagem das capacitações - Tonetto, Elci da Silva (2013)
The Bolsa Familia Program BFP is a public policy to transfer income which decreased the poverty condition of much of the population with low incomes. This program in its design was utilized a one dimensional measure to define the poor in Brazil, income. However, after 2006, added in its calculation multidimensional measures which are confirmed in this study as being the most appropriate to address the issues of poverty. What is sought with this study is to assess whether there was an increase in socioeconomic variables in the cities in the state in order to expand the capabilities of individuals and if the PBF fulfills its role as reducing inequalities both t he provision of income, and by providing opportunities to access two public policies are essential for human development, health and education. For both the descriptive statistics of the variables and a correlation matrix calculated from the data collected were used. The findings showed that there was significant improvement in the development of people in cities in the state social indicators. The Municipal Human Development Index, infant mortality rates, and lower rates of school leavers are some that sig nal improvements. The PBF has the role of public policy to transfer income, conditionality are an attempt to change adult behavior towards the care of children and adolescents. Income was considered crucial in determining the poor and extremely poor in Bra zil. However, the multiple dimensions analyzed in the Family Development Index gives a more comprehensive view of the deficiencies in the cities in the state. Taking income as single dimension analysis, the municipalities with better distribution concentra ted in the mountainous region of the state. The analysis when is held by the dimensions of the IDF the poverty there across all regions of the state, which confirms the multidimensionality as the best way of analyzing poverty.